The spectrum of N2 from 4, 500 to 15, 700 cm−1 revisited with pgopher. (November 2018) - Western, Colin M.; Carter-Blatchford, Luke; Crozet, Patrick; Ross, Amanda J.; Morville, Jérôme; Tokaryk, Dennis W.
Highlights: Fourier-transform spectrum of N2 first positive system from 9000 to 15, 700 cm −1 in ascii format. Illustrations of use of this reference spectrum to calibrate laser-excitation or absorption spectra. PGOPHER analysis of several B 3 Π g − A 3 Σ u +, B ′ 3 Σ u − − B 3 Π g, and W 3 Δu −B 3 Πg N2 bands with standard Hamiltonians, to simulate any part of the discharge spectrum between 4500 and 15, 700 cm −1 . Ab initio calculations of potential energy curves, transition moments and spin-orbit coupling constants for the B 3 Πg, A 3 Σ u +, B ′ 3 Σ u − and W 3 Δu states of N2 . Abstract: Using a reference molecular atlas to ensure self-consistency of wavelength calibration is widespread practice. Boesch & Reiners (Astronomy & Astrophysics 582 A43 (2015)) reported a line list from a discharge of molecular nitrogen from 4500 to 11, 000 cm −1 for this purpose. With a hollow-cathode discharge source, we have extended the experimental spectrum up to 15, 700 cm −1, to include the range of Ti:sapphire lasers, since the density of N2 lines is greater than atomic atlases in common use. Recognizing that experimental conditions can vary, we have also analysed the spectra (comprising several B 3 Π g − A 3 Σ u +, B ′ 3 Σ u − − B 3 Π g, and W 3 Δu −B 3 Πg N2 bands) with standard Hamiltonians, so that any part of the discharge spectrum in the range 4, 500–15, 700 cm −1 can be simulated. Parameters are given to do this with the spectral simulation and analysis packagepgopher . (C. Western, J. Quant. Spectrosc. Rad. Transf., 186, 221 (2016)). The analysis also included high-level ab initio calculations of potential energy curves, transition moments and spin-orbit coupling constants and these were used in preparing the model, extending the potential range of applicability. The results are available in a variety of formats to suit possible applications, including the experimental spectrum in ASCII, a detailed line list with positions and Einstein A coefficients, and a PGOPHER input file to synthesize the spectrum at selectable temperature and resolution. Graphical abstract: